2022
DOI: 10.3390/gels8020116
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of NLCs-Based Topical Erythromycin Gel: In Vitro Characterization and Antibacterial Assessment

Abstract: In the present study, erythromycin (EM)-loaded nanostructured lipid carriers (NLCs) were prepared by the emulsification and ultra-sonication method. EM-NLCs were optimized by central composite design using the lipid (A), pluronic F127 (B) and sonication time (C) as independent variables. Their effects were evaluated on particle size (Y1) and entrapment efficiency (Y2). The optimized formulation (EM-NLCs-opt) showed a particle size of 169.6 ± 4.8 nm and entrapment efficiency of 81.7 ± 1.4%. EM-NLCs-opt further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Thus forming a rigid layer of surfactant around the formed particles, preventing drug leaking and offering better drug housing and so better drug EE% ( Abdelhakeem et al, 2021 ). These results came in agreement with the results found by Zafar et al ( Zafar et al, 2022 ) who prepared NLCs-based erythromycin gel and revealed that the increase of Pluronic F127 (poloxamer 407) from 2% to 5% was accompanied by an increase in EE %. The positive effect of surfactants on EE% was also reported by Gadhave et al ( Gadhave and Kokare, 2019 ) and Kataria et al ( Kataria et al, 2022 ).…”
Section: Resultssupporting
confidence: 93%
“…Thus forming a rigid layer of surfactant around the formed particles, preventing drug leaking and offering better drug housing and so better drug EE% ( Abdelhakeem et al, 2021 ). These results came in agreement with the results found by Zafar et al ( Zafar et al, 2022 ) who prepared NLCs-based erythromycin gel and revealed that the increase of Pluronic F127 (poloxamer 407) from 2% to 5% was accompanied by an increase in EE %. The positive effect of surfactants on EE% was also reported by Gadhave et al ( Gadhave and Kokare, 2019 ) and Kataria et al ( Kataria et al, 2022 ).…”
Section: Resultssupporting
confidence: 93%
“…The antimicrobial efficiency of the generated nanoemulgel loaded with AZ against Escherichia coli (E. coli), Gram-negative bacteria was evaluated utilizing the agar diffusion technique according to Zafar et al with some adjustment [28]. Initially, the Petri dishes were sterilized at 160 • C for 60 min in a hot-air oven [29].…”
Section: Antibacterial Investigationmentioning
confidence: 99%
“…Afterward, ten milliliters of sterile nutrient agar media, sterilized in an autoclave at 121 • C for 15 min, were added to each plate. The microorganism was introduced into the plates after solidification under aseptic conditions [28]. A cork borer was used to make three millimeter-diameter cups in the plate, and the samples (placebo nanoemulgel, AZ-loaded gel, and AZ-loaded nanoemulgel) were then inserted to test their effectiveness [30].…”
Section: Antibacterial Investigationmentioning
confidence: 99%
“…A literature survey revealed that there are a limited number of studies aimed at developing an effective system for the improved ocular delivery of ERY. In a recent study, ERY-loaded nanostructured lipid carriers showed a prolonged release of 24 h with an enhanced corneal permeation [ 24 ]. In another study, a prolonged release of ERY (8 h release) was also observed from an in situ ocular gel formulation [ 25 ].…”
Section: Introductionmentioning
confidence: 99%